2021
DOI: 10.1101/2021.05.21.21257612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccination hesitancy model: The impact of vaccine education on controlling the outbreak in the United States

Abstract: The coronavirus outbreak continues to pose a significant challenge to human lives globally. Many efforts have been made to develop vaccines to combat this virus. However, with the arrival of the COVID-19 vaccine, there is hesitancy and a mixed reaction toward getting the vaccine. We develop a mathematical model to analyze and investigate the impacts of education on individuals hesitant to get vaccinated. The findings indicate that vaccine education can substantially minimize the daily cumulative cases and dea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…It also follows from the flow diagram that the system of differential equations governing the epidemic dynamic system satisfies: The interpretation of each parameter is given in Table 1. The model is a generalization of the classical SEIR deterministic model and is adopted from Oduro et al (2021). One main distinction from their work is that we assume that both recovery and vaccines provide immunity against the disease only for a limited period.…”
Section: Figure 1 Schematic Representation Of the Epidemic Modelmentioning
confidence: 99%
“…It also follows from the flow diagram that the system of differential equations governing the epidemic dynamic system satisfies: The interpretation of each parameter is given in Table 1. The model is a generalization of the classical SEIR deterministic model and is adopted from Oduro et al (2021). One main distinction from their work is that we assume that both recovery and vaccines provide immunity against the disease only for a limited period.…”
Section: Figure 1 Schematic Representation Of the Epidemic Modelmentioning
confidence: 99%
“…Therefore, it is in our view that religious people could believe more in conspiracy theories about vaccines and vaccination and could also believe that others are more prone to be influenced by other external factors, media included. While vaccine education can significantly decrease vaccine hesitancy rates (Oduro et al, 2021), education has been proved to be a predictor of TPE: when it comes to the ability to detect fake news, educated people perceive a greater gap between themselves and others (Corbu et al, 2020b, p. 11). Thus, TPE appears to be stronger in better educated individuals (Salwen, 1998).…”
Section: Predictors Of Third-person Perceptionsmentioning
confidence: 99%
“…For instance, 38% of those interviewed in France were hesitant toward COVID-19 vaccine where 10% were opposed to COVID-19 vaccination while the remaining 28% were undecided about getting COVID-19 vaccination [33]. In the United States (US), a report by the American Medical Association Journal hinted that skepticism toward vaccines that were being administered was on the rise [35]. This was further corroborated by the Kaiser Family Foundation COVID-19 vaccine monitoring which indicated that approximately 29% of health practitioners were reluctant to accept the vaccine [36].…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after WHO and Center for Disease Control (CDC) declared availability of COVID-19 vaccines, several epidemiological mathematical frameworks began to emerge with the aim of investigating whether vaccines will slow or end the COVID-19 pandemic as well as determining strategies that ensured optimal distribution of COVID-19 vaccines [41][42][43][44]. In the sequel, few epidemiological mathematical models have attempted to elucidate on the impact vaccine hesitancy played in the early roll-out of COVID-19 vaccines [33,35]. Some pertinent questions that relate to vaccine hesitancy have been investigated as far as COVID-19 vaccine roll-out is concerned.…”
Section: Introductionmentioning
confidence: 99%